Analysis of the Situation and Structure of Passenger Transport in Hungary - Nagy, Orsolya Bernadett (International Journal of Engineering and Management Sciences, 2018)
Traffic and transportation are important segments, as they contribute to the economy’s functioning, to mobility, trade and job creation. Transport per capita spending in recent years exceeded 10% of the total spending of the population. In the first part of my article, I review the characteristics and importance of passenger transport. In the subsequent chapters, I will show how significant are the trends and differences that can be discovered when analysing population spending on transport, car purchases and maintenance and passenger transport by age group and educational attainment.